2018
DOI: 10.1111/bju.14391
|View full text |Cite
|
Sign up to set email alerts
|

How can we expand active surveillance criteria in patients with low‐ and intermediate‐risk prostate cancer without increasing the risk of misclassification? Development of a novel risk calculator

Abstract: The use of a novel risk score for AS selection would result in an absolute increase of 10% in the number of patients eligible for this approach without increasing the risk of misclassification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 34 publications
(54 reference statements)
1
22
0
Order By: Relevance
“…Last but not least, the mentioned nomogram risk-threshold value of 25% was associated with significantly lower estimated frequency of csPCa that would be recommended for AS (11.3%), relative to the same four established AS inclusion criteria: PRIAS (∆:-14.3%), JH (∆:-5.9%), low risk (∆:-17.2%) and low risk or low volume ISUP GG2 (∆:-18.0%). These csPCa estimated rates are consistent with previous reports (6,7) and with Gandaglia et al (12) findings, which reported a minimum csPCa rate of 12-15%, despite the use of several AS inclusion criteria. However, it should be stated that our results were obtained by testing the predictive model in the population where it was developed.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Last but not least, the mentioned nomogram risk-threshold value of 25% was associated with significantly lower estimated frequency of csPCa that would be recommended for AS (11.3%), relative to the same four established AS inclusion criteria: PRIAS (∆:-14.3%), JH (∆:-5.9%), low risk (∆:-17.2%) and low risk or low volume ISUP GG2 (∆:-18.0%). These csPCa estimated rates are consistent with previous reports (6,7) and with Gandaglia et al (12) findings, which reported a minimum csPCa rate of 12-15%, despite the use of several AS inclusion criteria. However, it should be stated that our results were obtained by testing the predictive model in the population where it was developed.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, Gandaglia et al [ 12 ] combined PSA, cT stage, ISUP GG, number of positive cores, and PSA‐D, to develop a novel risk calculator to increase the number of AS‐eligible patients. With an AUC of 0.75, the Gandaglia et al [ 12 ] nomogram allowed the inclusion of ~10% more patients in AS compared to the PRIAS criteria. We therefore combined clinical, biopsy and mpMRI parameters to create a novel nomogram to further increase the number of AS‐eligible patients, without increasing the risk of csPCa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further options that may add value to AS patient selection include the use of multiparametric prostate magnetic resonance imaging, given its high negative predictive value for large high-grade cancers, and novel risk calculators that may increase the number of intermediate-risk patients eligible for AS without increasing the risk of misclassification [29]. However, recent studies have demonstrated that genomic classifiers are more accurate than MRI in predicting the presence of AP [30].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, several studies focus on the improvement of mpMRI findings in the active surveillance setting, for example, by implementing imaging findings in risk calculators. For instance, the risk calculator by Gandaglia et al [28] was designed to improve the selection of intermediate-risk PCa patients suitable for active surveillance by incorporating mpMRI findings. Summarizing the findings of this trial, the use of this risk score resulted in an absolute increase of 10% in the number of patients eligible for active surveillance and was validated recently [29].…”
Section: Implication Of Comprehensive Evaluation For Therapy Decisionmentioning
confidence: 99%